Essential urban design. A handbook for architects, designers and planners. - (:unkn) unknown (RIBA Publishing, 2021)
Shaping our cities, streets and public spaces, urban design informs the places we live. It is a complex multi-disciplinary process, requiring the input of a wide variety of stakeholders and design and construction professionals. Each urban project invariably throws up a new set of problems and strategic decisions for the design team. This guide distills the essential information required for the expert direction of the day-to-day work of urban design, from strategic design to masterplanning through to character assessment and collaboration. Compact and accessible with over 250 hand-drawn figures and plans, it's the perfect everyday companion for junior practitioners and experienced heads alike across the built environment.
Keywords: Städtebau; Entwurfsgrundlage; Entwerfen; Stadtgestaltung; Entwurfsprozess; Planungsprozess; Handbuch